Atlas of virtual colonoscopy comprehensive atlas and fundamentals - Dachman, Abraham H.; Laghi, Andrea (Springer, 2011)
Quot;Atlas of Virtual Colonoscopy" thoroughly revises and updates Abraham Dachman's bestselling first edition. Joined in this edition by co-editor Andrea Laghi, Dr. Dachman has expanded the focus of the text to cover fundamental topics of this rapidly evolving technology, including the history of virtual colonoscopy, a review of clinical trial data from throughout the world, and a presentation of clinical background information. Also included are chapters covering patient preparation and tagging, performing and reporting virtual colonoscopy, viewing methods, MR colonography, and computer.